INFLUENCE OF GEOGRAPHICAL FACTORS AND IINFRASTRUCTURE ON POVERTY IN THE BODEBEK REGION IN WEST JAVA PROVINCE - Lukman Hakim; Sumiyarti Sumiyarti; Sri Susilowati (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study intends to examine the influence of geographical and infrastructure factors on poverty in the Bogor, Depok and Bekasi (Bodebek) areas in West Java Province. To achieve the objectives of the penelitian, a regression method is used using the poverty variable as the dependent variable. While the dependent variables are divided into 4 (four) groups, which are divided into groups of variables of geography, infrastructure, population economy, and macroeconomic variables. The data used in this study came from the raw data of the Village Potential Data Collection (Podes) of West Java Province released by the Central Statistics Agency. The data period used is Podes data in 2011, 2014 and 2018. The scope of the study was at the village / kelurahan level with a household-level analysis unit. The observations cover 5 buffer areas of the State Capital in West Java Province, including Bekasi Regency, Bekasi City, Bogor Regency, Bogor City and Depok City. The total samples used from the six regions were 802 villages and sub-districts. The data analysis technique used is a panel data regression technique or model. The processing of research data was carried out using stata 13 software. The study concluded that factors of geography, infrastructure, economic conditions of the population as well as macroeconomic variables influenced or at least related to poverty in the areas of Bogor Regency, Bogor City, Depok City, Bekasi Regency and Bekasi City (Bodebek). The influence of each variable is different in each district and city in the Bodebek region